1993
DOI: 10.1111/j.1600-0714.1993.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral lesions in children born to HIV–1 positive women

Abstract: A cohort of 69 children born to HIV-1 positive women was studied to evaluate types, prevalences and relationships to clinical stages of HIV-1-related oral lesions. In addition, relationships among C. albicans biotypes, clinical features of oral candidiasis and HIV-1 disease were investigated. C. albicans biotypes did not correlate with clinical features of oral lesions, disease stages and CD4+ lymphocyte count. Of 8 patients with recurrent oral candidiasis, 4 changed clinical features and 5 changed biotype. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
4

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 17 publications
0
16
2
4
Order By: Relevance
“…In our study, the general prevalence of oral lesions, regardless of the use of HAART, was 31.4%, value below the results found in other studies with pediatric populations [4,17]. Khongkurtian et al in their study with pediatric population from Northern Thailand found prevalence of oral lesions of 48.9% [18].…”
Section: Discussioncontrasting
confidence: 80%
“…In our study, the general prevalence of oral lesions, regardless of the use of HAART, was 31.4%, value below the results found in other studies with pediatric populations [4,17]. Khongkurtian et al in their study with pediatric population from Northern Thailand found prevalence of oral lesions of 48.9% [18].…”
Section: Discussioncontrasting
confidence: 80%
“…An understanding of manifestati ons of oral disease is becoming increasingly important 3 . Oral examinati on is simple and non-invasive and some oral manifestati ons may be used to enhance early detecti on of HIV infecti on in vulnerable populati ons, elucidate progression of the disease and predict immune status, so that early interventi on can be provided [3][4][5][6][7][8] . The source and route of transmission in paediatric HIV infecti on is multi factorial.…”
Section: Resultsmentioning
confidence: 99%
“…In this study group there was a relatively infrequent presenta tion of gingivitis and absence of viral oral mucosal lesions, which contrasts with the high prevalence of such oral man ifestations in adult patients infected with HIV. Moniaci et al [13] investigated 69 children born to HIV-positive women for oral lesions. These authors found oral lesions in 28.9% of the children.…”
Section: Discussionmentioning
confidence: 99%